Oscillation of second order nonlinear impulsive difference equations with continuous variables - Karakoç, F. (Нелінійні коливання, 2013)
This paper is concerned with a second order nonlinear impulsive difference equation with continuous variable. By using a nonimpulsive inequality sufficient conditions for the oscillation of impulsive difference equation are obtained.